2004
DOI: 10.1021/jp0369950
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Alkyl Chains in Monolayer-Protected Au and Ag Clusters and Silver Thiolates:  A Comprehensive Quasielastic Neutron Scattering Investigation

Abstract: Temperature-dependent dynamics of monolayer-protected Au and Ag nanoclusters and silver thiolates have been investigated with quasielastic neutron scattering. The simplest motion in these systems is the uniaxial rotation of the chain, which evolves slowly with temperature. While longer chain monolayers (above C 8 ) on Au clusters are rotationally frozen at room temperature, dynamic freedom exists in lower chain lengths. In the superlattice solids of Ag clusters, the dynamics evolve slowly, and at superlattice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 53 publications
2
54
0
Order By: Relevance
“…The intermediate dynamics are characterized by a time ( = ℏ/Γ) of 6-7 ps, which is the typical time of both the conformational dynamics in the lipid chains and the rotational diffusion of methyl groups [11,35,36]. In Figure 4, the experimental EISF med , derived by the line shape analysis, for the POPC at = 248 and 273 K, are shown and compared with the results obtained at = 298 K for the liquid phase.…”
Section: Resultsmentioning
confidence: 99%
“…The intermediate dynamics are characterized by a time ( = ℏ/Γ) of 6-7 ps, which is the typical time of both the conformational dynamics in the lipid chains and the rotational diffusion of methyl groups [11,35,36]. In Figure 4, the experimental EISF med , derived by the line shape analysis, for the POPC at = 248 and 273 K, are shown and compared with the results obtained at = 298 K for the liquid phase.…”
Section: Resultsmentioning
confidence: 99%
“…Due to these unique properties, the synthesis strategies of AuNCs in water solution by some soft landing such as arylthiolates (Arnold and Reilly, 1998;Pradeep et al, 2004), dendrimers (Bao et al, 2007;Gröhn et al, 2000) have been reported in large volumes, and the AuNCs have been widely used in the fields of chemistry, biology, and materials (Wu and Jin, 2010). Recently, AuNCs have been successfully prepared and widely applied to fluorescence assay of enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore of interest to study the dynamical behaviour of these chains. Here we report the dynamics of alkyl chains in both isolated and superlattice systems with varying chain lengths, using QENS [22][23][24][25]. Isolated MPCs investigated are 6, 12 and 18 carbon n-alkyl chain thiolate-protected 4 nm diameter gold clusters while the superlattices are their silver analogues.…”
Section: Dynamics Of Alkyl Chains In Monolayer-protected Metal Clustementioning
confidence: 99%